2016
DOI: 10.1242/jcs.184424
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes bind to autotaxin and act as a physiological delivery mechanism to stimulate LPA receptor signalling in cells

Abstract: Autotaxin (ATX; also known as ENPP2), the lysophospholipase responsible for generating the lipid receptor agonist lysophosphatidic acid (LPA), is a secreted enzyme. Here we show that, once secreted, ATX can bind to the surface of cell-secreted exosomes. Exosomebound ATX is catalytically active and carries generated LPA. Once bound to a cell, through specific integrin interactions, ATX releases the LPA to activate cell surface G-protein-coupled receptors of LPA; inhibition of signalling by the receptor antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 25 publications
5
49
0
Order By: Relevance
“…Such an event could hypothetically lead to LPA-bound ATX at the cell surface, after which ATX would release LPA and activate LPARs. Indeed, the authors indicated that it was by this mechanism that ATX yielded activation of LPA 1 and LPA 3 in the employed in vitro experimental setup [29]. Taken together, the evidence is consistent with a role of ATX as an LPA carrier, transporting LPA to distal locations from those where LPC can be taken.…”
Section: Autotaxin Catalytic and Non-catalytic Functionssupporting
confidence: 58%
See 1 more Smart Citation
“…Such an event could hypothetically lead to LPA-bound ATX at the cell surface, after which ATX would release LPA and activate LPARs. Indeed, the authors indicated that it was by this mechanism that ATX yielded activation of LPA 1 and LPA 3 in the employed in vitro experimental setup [29]. Taken together, the evidence is consistent with a role of ATX as an LPA carrier, transporting LPA to distal locations from those where LPC can be taken.…”
Section: Autotaxin Catalytic and Non-catalytic Functionssupporting
confidence: 58%
“…Although these observations appear contradictory, the loop insertions could have induced structural changes destabilising the orthosteric site, and resulting in catalytically inactive ATX without just occluding substrate trafficking through the tunnel. Interestingly, a recent study indicated that active ATX can bind to the surface of secreted exosomes and carry LPA [29]. Such an event could hypothetically lead to LPA-bound ATX at the cell surface, after which ATX would release LPA and activate LPARs.…”
Section: Autotaxin Catalytic and Non-catalytic Functionsmentioning
confidence: 99%
“…Here, we show that CCL18 functions as bridging adaptor for GBM EVs, and CCL18 expression has been identified as an important prognostic factor in GBM [90]. Recently, it was shown that EVs can also be decorated by autotaxin resulting in binding to integrins expressed on cell surfaces [32]. Similarly, it was reported that heparan sulphates exposed on EVs can bind to fibronectin, serving as a connecting molecule to heparan sulphates expressed on cell membranes [34].…”
Section: Discussionmentioning
confidence: 85%
“…We observed that pretreatment of cells with heparin reduces EV uptake to a lesser extent than pretreatment of EVs with heparin (data not shown), suggesting that both mechanisms (direct heparin sulphate- and CCR8-mediated endocytosis) can occur simultaneously. An important consequence of the ‘connectokine’ model is that it implies a complex level of regulation of EV transfer, perhaps similarly as observed for decoration of EVs with autotoxin [32] or fibronectin.…”
Section: Discussionmentioning
confidence: 99%
“…One method for miRNA secretion from the cell is via exosomes, 30-100 nm vesicles that are released when multivesicular endosomes fuse with the plasma membrane (8,9). Exosomes can also contain DNA, RNA, proteins, lipids, and enzymes that metabolize lipids (10)(11)(12). Exosome secretion appears to be a signature of tumor cell aggressiveness, which serves as communication with the microenvironment to precondition tissue and facilitate tumorigenesis (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%